The Nature of Error Consistency in Apraxia of Speech and Aphasia with Phonemic Paraphasia - Bislick, Lauren Patricia (My University, 2015)
Effective treatment programs for communication disorders are based on the underlying nature of the impairment; therefore, accurate diagnosis is critical. In some cases, however, reliable and valid methods of differentially diagnosing disorders with similar behavioral profiles are lacking. This is particularly true of acquired apraxia of speech (AOS) and aphasia characterized by frequent occurrences of phonemic paraphasia (PP). The differential diagnosis of AOS and aphasia with PP is challenging because both disorders result from left hemisphere stroke and share clinical characteristics. Therefore, the identification of characteristics that pattern uniquely to each disorder is important. One way in which to strengthen the current diagnostic process is to examine the validity of diagnostic criteria used to inform differential diagnosis. The current criteria proposed to differentiate AOS from aphasia with PP include: 1) slow speech rate characterized by prolonged segment and intersegment durations, 2) sound distortions, 3) distorted sound substitutions, 4) prosodic abnormalities, and 5) relatively consistent errors in regard to error location and error type. Of these characteristics, error consistency is the most controversial. Error consistency refers to whether or not errors are relatively consistent from trial to trial in regard to the location of errors within a word (e.g., word initial) and the type of errors produced (e.g., distortions vs. substitutions). Investigations comparing the nature of error consistency in AOS and aphasia with PP have revealed conflicting results. These studies, however, differ in important methodological areas, making it difficult to draw conclusions about the nature of error consistency in these two populations. Furthermore, previous studies suggest that error consistency may be influenced by a number of variables, such as error rate, severity of impairment, and stimulus presentation condition. This study sought to further examine the nature of error consistency in a group of 10 individuals with AOS and concomitant aphasia and a group of 11 individuals with aphasia with PP. Specifically, this study examined group differences in the consistency of error location and error type during the repetition of two-, three-, and five-syllable words. The influence of error rate, severity of impairment, and stimulus presentation condition on measures of error consistency was also examined, as well as group differences in the types of errors produced. Results suggest that consistency of error location does not differentiate group performance, whereas the variability of error type does. In particular, individuals with AOS and aphasia demonstrate more variable errors compared individuals with aphasia with PP. Results also indicate that the consistency of error location is influenced by error rate and severity of impairment. Stimulus presentation condition, however, did not appear to influence group performance on either measure of error consistency. Lastly, results of an error type analysis show that individuals with AOS and aphasia demonstrate significantly more phonetic errors compared to individuals with aphasia with PP. In conclusion, results do not support the use of error consistency as a valid measure in which to differentiate individuals with AOS and aphasia from individuals with aphasia with PP.
Thesis (Ph.D.)--University of Washington, 2015
Keywords: Aphasia; Apraxia of Speech; Differential Diagnosis; Error Consistency; Phonemic Paraphasia; Primary Characteristics; Speech therapy; speech